General Overview on Selecting and Drafting Construction Contract Disputes Resolution - Meria Utama; Irsan Irsan (Sriwijaya Law Review, 2018)
A good international contract as the experts considered is the most complicated one the parties must draft carefully. It involves many stakeholders and containing documents to attach likewise financial judgment, technical specifications, work scope, rights, obligation, responsibility and other external factors which are beyond the parties’ consideration. A good design contract will prevent the parties from disputes. The dispute settlement mechanisms should be explicitly stated in the international construction contract. The nullity of the choice dispute settlement mechanisms or in the absence of the choice dispute settlement mechanisms and also the unperformed of the contract purposes will not prevent the dispute from being occurred. The most common process to resolve disputes is through litigation, but the process takes time, energy and funding. The method of alternative dispute resolution (ADR) such as mediation, conciliation, mini-trial, arbitration or other ADR techniques eradicate all the obstacles above. The question arises then, how the parties select the best alternative disputes settlement mechanism and how it should be drafted in their contract. Normative legal research is the method employed to respond the problems. Therefore, this article will elaborate the methods that will effectively settle the constructions disputes and mechanism in drafting construction contract disputes resolutions provisions